Experimental Investigation on the Separation Performance for a New Oil-Water Separator - Zhan, Min; Yang, Wanyou; Zhang, Fenghui; Luo, Changhua; Wu, Huaxiao; Guo, Peiwen; Shen, Qiong; Zeng, Xiaobo; Yan, Changqi (Frontiers in Energy Research, 2021)
In order to reduce the cost of oil production, it’s necessary to promote the development of cyclone for oil-water separation with the increasing of the water content of the production. However, there exist some limitations and disadvantages for the conventional separation device including bulky settling tanks and hydrocyclones. In this paper, a novel axial inlet separator with reverse flow outlets and downstream flow outlet was introduced. Additionally, an experimental system was designed and fabricated to investigate the effects of inlet flow rate, oil fraction and split ratio on separation performance. The separator keeps high separation efficiency in the experimental range, namely, the water flow rate (4~7 m3/h), and oil fraction (1%~10%). Furthermore, the results show that higher water flow rate and oil fraction hamper the separation efficiency and the change in pressure drop of the separator was analyzed. The split ratio is a serious operating parameter and larger split ratio is conducive to separation performance.